The Role of TVRI in Maintaining Interreligious Harmony (An Analytical Study at the Faculty of Social Sciences, State Islamic University of North Sumatra) - Hasibuan, Dini Amalia; Shila, Nadia Frety; Rudhani, Goenersya Haidar; Sazali, Hasan (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the role of TVRI in maintaining interreligious harmony in Indonesia. As a public broadcasting institution, TVRI is expected to play a strategic role in building and preserving harmony among religious communities within a multicultural society. The results show that TVRI has actively presented programs that emphasize the values of diversity and interreligious tolerance. These programs include coverage of religious activities from various denominations, interfaith dialogues, and educational broadcasts that encourage mutual understanding among religious communities. In addition, TVRI provides space for the representation of all religions present in Indonesia. However, there are several limitations in TVRI’s role, such as the limited duration of coverage related to religious diversity compared to other news coverage, which may cause some audiences to be less interested in watching these broadcasts for extended periods. Furthermore, some programs may lack depth in addressing more complex issues of religious diversity. Therefore, improvements in both the quality and quantity of such programs are needed so that TVRI can be more effective in maintaining interreligious harmony. This study concludes that TVRI plays a significant role in maintaining interreligious harmony in Indonesia.